A new species of Guzmania (Bromeliaceae) from Southern Ecuador - Gouda, Eric J.; Manzanares, José M.; Takizawa, Hiroyuki (Phytotaxa, 2017)
A new species of Guzmania from Ecuador, Province El Oro, closely related to G. teuscheri Smith (1960: 86), is described and illustrated here. It can easily be confused with this species, especially in herbarium specimen, in which the colour and structure of petals are lost.